Temperature-dependent kinetics and saturation of OH formation during solar wind proton implantation - Qi-ao Chen; Wen Yu; Hao Yan; Tian Zhang; Hong Tang; Xiongyao Li (Earth and Planetary Science Letters, 2026)

Re-appraisal of the Mesozoic male cone Ixostrobus Raciborski (Czekanowskiales) based on new material from the Qaidam Basin, NW China: New insights into systematics, diversity and spatio-temporal distribution - Hong-Yu Chen; Yong-Dong Wang; Li Zhang; Yan-Bin Zhu; Ao-Wei Xie; Peng-Cheng An; Dieter Uhl (Review of Palaeobotany and Palynology, 2026)

Electrostatically assembled gold nanocluster-enhanced porphyrinic metal-organic framework nanozymes for oxygen-boosted photodynamic therapy of hypoxic tumors - Ao He; Juan Zhou; Jing Zhu; Guojing Hong; Minglan Fan; Yuyan Bao; Rong Li; Manxiao Cheng; Xiang Ran (Journal of Photochemistry and Photobiology B: Biology, 2026)

Trophic dynamics of parrotfish in a degraded coral reef ecosystem in the Xisha Islands, South China sea - Jinfa Zhao; Teng Wang; Yu Liu; Hong Li; Huaxue Liu; Hongyu Xie; Jianzhong Shen; Yayuan Xiao; Xuefu Ao; Hai Huang; Yong Liu; Qiuying Han (Environmental Research, 2026)

Single-precursor-enabled surface/near-surface engineering for stabilizing oxygen redox in high-voltage Li-rich layered cathodes - Yujia Zhang; Shi Gu; Fuliang Guo; Pengcheng Yuan; Ao Li; Nan Zhang; Liang Yin; Hong Li (Chemical Engineering Journal, 2026)

Concentration-dependent variation in carbon allocation and microbial assembly in chain elongation microbiota: Comparative effects of acetate, ethanol, and lactate - Ya-Ning Song; Li-Juan Chai; Ling Ao; Jun-Lan Mei; Yu-Long Li; Zhen-Ming Lu; Xiao-Juan Zhang; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Bioresource Technology, 2026)

Interfacial hydrogen bonding as a key driver for selective phenolic compounds removal via Mg(OH)2-catalyzed peroxymonosulfate activation - Yuan Ding; Jiachun Cao; Shiting Li; Hong Huang; Honggen Peng; Xiaoxiao Fu; Chunyang Nie; Zhimin Ao (Chemical Engineering Journal, 2026)

Continuous Diurnal–Nocturnal Observation of Atmospheric Aerosols: Mechanisms, Challenges, and the Prospects of AI Empowerment - Huizheng Che; Yu Zheng; Lei Li; Ke Gui; Hengheng Zhao; Junli Jin; Xiaochun Zhang; Xiang’ao Xia; Yupeng Wang; Zhiwei Xia; Yucong Miao; Yaqiang Wang; et al. (Journal of Meteorological Research, 2026)

Ginsenosides mitigate multi-organ aging: mechanistic insights from a preclinical systematic review and meta-analysis - Ao Li; Hua-Ze Wu; Die-Yi Chen; Yu-Xin Gao; Xiao-Qiang Xiang; Qing-Hui He; Hong-Yan Ma; Dan Tang (Critical Reviews in Food Science and Nutrition, 2026)

Deep carbon cycling in continental subduction zones - Sheng-Ao Liu; Wan-Yu Sun; Yuan-Ru Qu; Hong-Li Yang (Lithos, 2026)

Comparative analysis of chemical compositional profiles and immunomodulatory activity of ginseng in different habitats - Chen-Yue Zeng; Quan-Kuan Dai; Hua-Ze Wu; Ao Li; Yong-Lin Chen; Qing-Hui He; Dan Tang; Hong-Yan Ma (Journal of Natural Medicines, 2026)

Experimental study on the wave mitigation characteristics of a grid-type flexible-membrane breakwater under regular waves - Chuan-Rui Li; Jing-Ping Wu; Ming-Liang Cai; Jun-Ao Kang; Chang-Zhe Chen; Hong Fan; Chen-Xia Liu; Shi-Yu Yang; Zi-Wen Xu (Ocean Engineering, 2026)

Control of mantle infertility on cross-arc geochemical diversity revealed by zinc isotope systematics - Chun Yang; Hong-Yan Li; Sheng-Ao Liu; Yoshihiko Tamura; Sergey Smirnov; Jeffrey G. Ryan; Yi-Gang Xu (Earth and Planetary Science Letters, 2026)

Revisiting slope-area thresholds for gully initiation: a systematic review and meta-analysis - Yang Yang; Guanghui Zhang; Cheng’ao Li; Hong Cheng; Yingna Liu (Earth-Science Reviews, 2026)

A Genome-based Machine Learning Model for Safety Assessment of Microorganisms - Wei Lei; Li-Hua Liu; Hong Huang; Yu Zhang; Kuo Zhang; Tian Yu; Junyang Huang; Shuqi Wang; Ao Jiang (Probiotics and Antimicrobial Proteins, 2026)

MsWIP3 functions as a transcriptional regulator affecting alfalfa (Medicago sativa) response under saline -alkali stress - Wang Kexin; Wang Zheyuan; Zhang Hongjiao; Yao Tongtong; Xu Jingjing; Zhang Hongrui; Qi Siyue; Liu Hongzheng; Li Xin; Ao Hong; Zhang Huihui (Plant Cell Reports, 2026)

Altitude, land use and precipitation regimes drive key factors of lake nitrous oxide emission on large geographic scales - Ao Tang; Xiaoying Yang; Yongqiang Zhou; Gang Li; Zhirong Yu; Hong Yang; Bingshuai Li; Erik Jeppesen; Qichao Zhou (Water Research, 2026)

Subspecies-specific epigenetic remodeling drives differential cold adaptation in geng/xian rice - Dong-Ao Li; Xiao-Long Xu; Yu-Hong Luo; Zu-Wen Zhou; Yong-Qing Qian; Qian Tang; Xi-Tong Zhu; Jia-Ming Song; Ling-Ling Chen (Plant Science, 2026)

Corrigendum to “Both target-site and non-target-site resistance mechanisms confer mesosulfuron-methyl resistance in Silene conoidea L.” [Pesticide Biochemistry and Physiology 218(2026) 106905] - Xinhui Xue; Hailan Cui; Shen'ao Hu; Hong Ma; Shouhui Wei; Hongjuan Huang; Xiangju Li; Zhaofeng Huang (Pesticide Biochemistry and Physiology, 2026)

Both target-site and non-target-site resistance mechanisms confer mesosulfuron-methyl resistance in Silene conoidea L. - Xinhui Xue; Hailan Cui; Shen'ao Hu; Hong Ma; Shouhui Wei; Hongjuan Huang; Xiangju Li; Zhaofeng Huang (Pesticide Biochemistry and Physiology, 2026)

From inhalation to systemic damage: Decoding the mechanistic cascade of silica nanoparticle-induced multi-organ toxicity - Jia-Qi Ban; Li-Hong Ao; He-Qun Gu; Yun-Geng Wei; Qiong Tian; Xiu He; Hua Zhao; Jun Li (Toxicology, 2026)

iHalo: a genome-based machine learning model using k-mer for halophiles identification - Li-Hua Liu; Yu Zhang; Wei Lei; Hong Huang; Kuo Zhang; Zhiqian Zhang; Shuqi Wang; Ao Jiang (World Journal of Microbiology and Biotechnology, 2026)

Anti-epileptic effect of saikosaponin a by inhibiting ferroptosis via the IL-17/Akt/ERK signaling pathway in the temporal lobe epilepsy model - Ping-Ping Li; Wen-Wen Wang; Jing-Tao Wang; Zi-Ao Xu; Xue-Fei Ji; Liao Guan; Lei Ye; Hong-Wei Cheng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

QTL analysis of single-segment substitution lines dissected from a rice CSSL-Z668 and fine-mapping of qGL3.4 for grain length - Si-Qian Xiang; Yu-Zhu Tao; Zhao-Peng Yu; Zhuo-Wen Zhao; Han Zhang; Qiao-Long Li; Lu Li; Ao-Ni Xiang; Jing-Hong Xu; Fan Zhang; Xu Yan; Zheng-Lin Yang; et al. (Euphytica, 2026)

RFAGB model: A new machine learning model for microplastic inversion based on remotely sensed data in Bohai Sea - Ao Shen; Yongzheng Ma; Yuan Li; Pingping Hong; Zhiguang Niu; Ying Zhang; Jingen Xiao; Dianjun Zhang (Water Research, 2025)

A comparative study on catalytic activation of peroxymonosulfate over polytype 2H-MoS2 and 3R-MoS2 - Shiting Li; Yuehan Wang; Chang Cai; Hong Huang; Honggen Peng; Xiaoxiao Fu; Zhimin Ao; Chunyang Nie (Journal of Environmental Chemical Engineering, 2025)

Temperature dependency of methane emissions from alkaline wetlands under warming: Synergistic effects of soil properties and microbial communities - Dawen Gao; Xiaofei Gong; Feng Li; Zheng Huang; Ao Xu; Tianfu Yang; Hong Liang (Environmental Research, 2025)

Low-temperature plasma mutagenesis breeding of Chlorella sorokiniana mutant strains for efficient carbon sequestration - Dong-Ao Li; Hong Zhang; Guang-Hui Xu; Jie Shen; Qing Huang (Bioresource Technology, 2025)

WS2/CuO-based non-enzymatic sensor for the detection of glucose in sweat - Dujuan Li; Mingzhu Yang; Wenhui Li; Ao Wang; Xinyi Wang; Liang Hong; Linxi Dong; Hong Xu; Gaofeng Wang (Analytica Chimica Acta, 2025)

Evolution of water-carrying capacity and response law of land space pattern in the Three Gorges Reservoir Area - Feng Zhou; Wanshun Zhang; Xin Liu; Hong Peng; Han Xia; Ao Li; Gang Chen; Hao Wang (Land Use Policy, 2025)

Deep carbon sink in the East Asian mantle and its impact on atmospheric CO2 drawdown since the Cretaceous - Chun Yang; Sheng-Ao Liu; Hong-Yan Li; Yi-Gang Xu (Earth and Planetary Science Letters, 2025)

Effect of Dandelion Root Extract on Growth, Biochemical Indices, Antioxidant Capacity, Intestinal Histomorphology and Microbiota in Micropterus salmoides - Peng-Ao Liu; Hong-Ling Yang; Jian Huang; Fen Li; Ke-Yun Huang; Zi-Xin Liu; Guo-He Cai; Yun-Zhang Sun (Fishes, 2025)
Intensive aquaculture systems face challenges including compromised immune function and hepatointestinal damage in cultured species. Therefore, it is urgent to seek effective feed additives to strengthen health and immunity in intensive aquaculture. This study evaluated the potential of dandelion root extract (DRE) for improving growth performance, immune response, and hepatointestinal health in juvenile largemouth bass (Micropterus salmoides). Fish were fed diets supplemented with 0.05% (DRE1), 0.1% (DRE2), and 0.15% (DRE3) DRE for 42 days. The results showed that DRE supplementation had no significant effect on growth performance indicators (p > 0.05). However, compared to the control group, the DRE2 and DRE3 groups exhibited significantly reduced AST and ALT activities (p

Electrokinetic-H-nZVI/PS remediation of petroleum hydrocarbon contaminated soil: Mechanism and NaH2PO4/Na2HPO4 enhancement - Yong-Tao Li; Qian Chen; Jian-ying Xiao; Yu Tang; Ao Yang; Xi Li; Hong Liang (Chemical Engineering Journal, 2025)

Insights into Mn-doped biochar induce peroxymonosulfate activation for phenol degradation: The overlooked significance of C-O-Mn - Hong Meng; Junhui Zhou; Chunyang Nie; Wenhao Li; Didi Li; Yongqing Zhang; Zhimin Ao (Journal of Hazardous Materials, 2025)

New micro- and macro- perspective on the removal process of 1H-benzotriazole by UV/PDS: Degradation mechanism, kinetics and multi-factor impact on removal efficiency - Juan Dang; Li-ao Gao; Xue Jia; Xiao-meng Zhang; Hong-jin Wu; Shi-bo Zhang; Qing-zhu Zhang; Shuai Tian (Journal of Environmental Management, 2025)

Designed amino acid-based deep eutectic solvents as a platform to functionalize biomedical elastomers by polyaddition reactions - Ao Zhen; Ao Wang; Xirui Long; Xiao Wang; Nan Sheng; Qing Tang; Jiehua Li; Hong Tan; Feng Luo; Zhen Li (Chemical Engineering Journal, 2025)

Global analysis of fungal biosynthetic gene clusters reveals the diversification of diketopiperazine biosynthesis - Bin Wei; Ti-Ti Ying; Hua-Wei Lv; Zhen-Yi Zhou; Hai Cai; Gang-Ao Hu; Hui-Min Liang; Wen-Chao Yu; Yan-Lei Yu; Ai-Li Fan; Kui Hong; Xing-Nuo Li; et al. (Bioresource Technology, 2025)

An improved coupled water quantity–quality–ecology model incorporating diurnal cycle as a key factor affecting algal blooms and application in large rivers - Xin Liu; Wanshun Zhang; Yue Wang; Hong Peng; Anna Jiang; Ao Li; Xu Zhang; Hao Wang (Journal of Environmental Management, 2025)

Growth, biochemical indexes, and intestinal microbiota response of red tilapia (Oreochromis spp.) under different densities and feeding frequencies in the land-based aquaculture tank - Yu-Xiang Xie; Jun-Neng Liang; Gen Kaneko; Lu-Ting Wen; Yi-Jian Li; Qui-Wei Ao; Li-Ming Huang; Qiong Yang; Zhen-Ping Liao; Xue-Ming Yang; Hong-ping Zhang; Lin-Yuan Jiang; et al. (Aquaculture, 2025)

Complex function method considering rock strength for determining critical warning deformation of deep-buried complex cavern - Ao-Ying Luo; Li Zhuo; Huai-Zhong Liu; Hong-Qiang Xie; Nu-Wen Xu; Ming-Li Xiao; Yong-Jian Shuai (Tunnelling and Underground Space Technology, 2024)

The resistance mechanism of humic acids and proteins in soluble microbial products from activated sludge against silver nanoparticles - Jia Kang; Yi-hang Wang; Yao-wen Zhang; Chu-qiong Song; Ao-di Wang; Ning Zhou; Yi-hui Zhang; Fa-zhan Li; Shu-li Liu; Li-sha Liu; Gang-fu Song; Bai-hong Wang (Journal of Environmental Chemical Engineering, 2024)

Synthesis and fabrication of magnetically separable phosphate-modified magnetic chitosan composites for lead(II) selective removal from wastewater - Yaoyao Huang; Yuqi Peng; Guizhi Zhang; Zhengsijia Wu; Juan Li; Wei Ding; Hong Li; Yanyan An; Liang Ao; Yu Shen; Huaili Zheng (Environmental Research, 2024)

Improving hydrological process simulation in mountain watersheds: Integrating WRF model gridded precipitation data into the SWAT model - Anna Jiang; Wanshun Zhang; Xin Liu; Feng Zhou; Ao Li; Hong Peng; Hao Wang (Journal of Hydrology, 2024)

Catalytic hydroconversion of aryl ethers to polycyclic alkanes over Ni@MCM-41/β composite zeolite: Aromatic α-carbon activation and hydrogen transfer mechanisms - Guang-Hui Liu; Wen-Ao Shi; Jun Li; Han Wang; Ai-Min Wang; Yu-Hong Kang; Yong Gao; Ni Bai; Jie Kang; Chen Shi; Xian-Yong Wei (Fuel, 2024)

Clinicopathological characteristics and prognosis of Epstein-Barr virus–associated gastric cancer - Lin-lin Li; Ao-yang Yu; Mei Zhu; Lu-yao Ma; Meng-han Cao; Wen-lou Liu; Xiao-bing Qin; Chao Gao; Zheng-xiang Han; Hong-mei Wang (Archives of Virology, 2024)

Metagenomic insights into carbon and nitrogen cycling in the water-land transition zone of inland alkaline wetlands - Dawen Gao; Ao Xu; Yupeng Zhang; Fengqin Liu; Huiju Li; Hong Liang (Science of The Total Environment, 2024)

Arsenic disturbs neural tube closure involving AMPK/PKB-mTORC1-mediated autophagy in mice - Xiujuan Li; Gexuan Li; Shuo Cui; Yue Hou; Zelin Li; Ziyi Yan; Tingjuan Huang; Taoran Zhao; Hongkai Su; Bingrui Zhou; Juan Zhang; Ruifang Ao; et al. (Food and Chemical Toxicology, 2024)

The earliest microblade site 6800 years ago reveals broader social dimension than previous thought at the central high altitude Tibetan plateau - Yahui Qiu; Peixian Shu; Hong Ao; Yunxiang Zhang; Qi Wei; Xingwen Li; Honghai Chen; Hong Wang; Stanley H. Ambrose (Quaternary Science Reviews, 2024)

Quantitative analysis of key components in Qingke beer brewing process by multispectral analysis combined with chemometrics - Xianjiang Zhou; Li Li; Jia Zheng; Jianhang Wu; Lei Wen; Min Huang; Feng Ao; Wenli Luo; Mao Li; Hong Wang; Xuyan Zong (Food Chemistry, 2024)

Advances in the study of silica nanoparticles in lung diseases - Li-Hong Ao; Yun-Geng Wei; Hong-Ru Tian; Hua Zhao; Jun Li; Jia-Qi Ban (Science of The Total Environment, 2024)

A novel antimony metallochaperone AntC in Comamonas testosteroni JL40 and its application in antimony immobilization - Lijin An; Mingzhu Xu; Mengjuan Hong; Lipeng Zhao; Ao Wei; Xiong Luo; Kaixiang Shi; Shixue Zheng; Mingshun Li (Science of The Total Environment, 2024)

Mechanical robust, adhesive, self-healable and biodegradable protein-based electronic skin sensors for smart elderly care - Ying-Ao Zhang; Chen-Yu Wang; Xiao-Xue Wang; Meng Yin; Ke Wang; Da-Wei Zhou; Hong-Long Zheng; Shou-Shan Yu; Shuang Li; Ke-Zheng Chen; Sheng-Lin Qiao (Chemical Engineering Journal, 2024)

Genetic polymorphisms of purinergic P2Y2 receptor were associated with the susceptibility to essential hypertension in Chinese postmenopausal women - Ao Li; Chaopeng Xiong; Chengxin Gong; Mengyang Gou; Yaqun Wang; Yuping Yang; Hong Xu (Purinergic Signalling, 2023)

Efficient nitrogen removal from mature landfill leachate by single-stage partial-nitritation anammox using expanded granular sludge bed - Wenbo Yang; Lang Cheng; Hong Liang; Ao Xu; Yuqi Li; Mohammad Nabi; Huan Wang; Jiachen Hu; Dawen Gao (Journal of Environmental Management, 2023)

Evolution hydrothermal aging mechanism for Ag/CeO2 catalysts in regeneration of catalytic diesel particulate filter with DFT calculation - Zonglin Li; Hong Ni; Pan Wang; Zhengtao Liu; Chengcheng Ao; Lidong Zhang; Yunjing Wang (Environmental Science and Pollution Research, 2023)

Distinct chemistry between Zn and Li at varied temperature - Qing Li; Hu Hong; Xun Guo; Jiaxiong Zhu; Yue Hou; Chao Liu; Donghong Wang; Guojin Liang; Yuwei Zhao; Ao Chen; Hongfei Li; Binbin Dong; et al. (Science Bulletin, 2023)

New radiocarbon dates and the prehistoric human occupation at the Lake Qinghai Basin, northeast Tibetan Plateau - Yahui Qiu; Peixian Shu; Hong Ao; Yunxiang Zhang; Xingwen Li; Hong Wang (Quaternary International, 2023)

Risks of applying mobilising agents for remediation of arsenic-contaminated soils: Effects of dithionite–EDTA and citric acid on arsenic fractionation, leachability, oral bioavailability/bioaccessibility and speciation - Xiao-Chen Chen; Cong-Cong Yao; Ao Wang; Zeng-Di Zhang; Long-Zhao Chen; Jian-Yu Zhang; Xian-Hua Liu; Hong-Bo Li (Journal of Hazardous Materials, 2023)

Municipal solid waste incineration (MSWI) fly ash could be used as a catalyst for pyrolysis of oil-based drill cuttings from shale gas exploitation industry - Tengtun Xu; Li'ao Wang; Hong Wu; Debin Jiang; Ning Qi; Zhenqiong Gou (Journal of Cleaner Production, 2023)

Multi-functional bilayer carbon structures with micrometer-level physical encapsulation as a flexible cathode host for high-performance lithium-sulfur batteries - Yonghui Xie; Juan Ao; Li Zhang; Yeqing Shao; Hong Zhang; Shuying Cheng; Xinghui Wang (Chemical Engineering Journal, 2023)

Sweet tea ( Lithocarpus polystachyus rehd.) as a new natural source of bioactive dihydrochalcones with multiple health benefits - Ao Shang; Hong-Yan Liu; Min Luo; Yu Xia; Xiao Yang; Hang-Yu Li; Ding-Tao Wu; Quancai Sun; Fang Geng; Ren-You Gan (Critical Reviews in Food Science and Nutrition, 2022)

Seasonal rainfall patterns in stable carbon isotopes in the Mu Us Desert, northern China during the early and middle Holocene - Peixian Shu; Hong Wang; Weijian Zhou; Hong Ao; Dongfeng Niu; Xiaohao Wen; Baosheng Li (Climate Dynamics, 2021)

Contribution of Cathepsin L to Autolysis of Sea Cucumber Stichopus japonicus Intestines - Jia-Nan Yan; Xiao-Kun Guo; Yue Tang; Ao-Ting Li; Zhi-Mo Zhu; Xiao-Qian Chai; Xiu-Hong Duan; Hai-Tao Wu (Journal of Aquatic Food Product Technology, 2019)

Identifying potentially common genes between dyslipidemia and osteoporosis using novel analytical approaches - Xu Lin; Cheng Peng; Jonathan Greenbaum; Zhang-Fang Li; Ke-Hao Wu; Zeng-Xin Ao; Tong Zhang; Jie Shen; Hong-Wen Deng (Molecular Genetics and Genomics, 2018)

New fossils of the Early Pleistocene Equus huanghoensis (Equidae, Perissodactyla) from Nihewan in Hebei province of China - YongXiang Li; YunXiang Zhang; BoYang Sun; Hong Ao; XiangXu Xue (Science China Earth Sciences, 2016)

Antithrombotic lipids from Semen Persicae - Nian-Yun Yang; Li Liu; Wei-Wei Tao; Jin-Ao Duan; Xun-Hong Liu; Su-Ping Huang (Natural Product Research, 2011)

New eolian red clay sequence on the western Chinese Loess Plateau linked to onset of Asian desertification about 25 Ma ago - Xiaoke Qiang; Zhisheng An; Yougui Song; Hong Chang; Youbin Sun; Weiguo Liu; Hong Ao; Jibao Dong; Chaofeng Fu; Feng Wu; Fengyan Lu; Yanjun Cai; et al. (Science China Earth Sciences, 2011)